Science, technology & innovation policy review : Dominican Republic (UN New YorkUS, 2012)
Offers an up-dated diagnosis of the effectiveness of STI policies, programmes and instruments; facilitates the strengthening of those policies and measures by integrating them into the national development progress; and contributes to improve technological capacity, encourge innovation and incorporate greater added value into production.
Bibliography: p.103-106.